Cytocompatibility of regenerated silk fibroin film: a medical biomaterial applicable to wound healing - Liu, Tie-lian (Zhejiang University Press, 2010)

(untitled)
Objective: To explore the feasibility of using regenerated silk fibroin membrane to construct artificial skin substitutes for wound healing, it is necessary to evaluate its cytocompatibility. Methods: The effects of regenerated silk fibroin film on cytotoxicity, adhesion, cell cycle, and apoptosis of L929 cells, growth and vascular endothelial growth factor (VEGF) expression of ECV304 cells, and VEGF, angiopoietin-1 (Ang-1), platelet-derived growth factor (PDGF) and fibroblast growth factor 2 (FGF2) expression of WI-38 cells were assessed by 3-(4,5)-dimethylthiahiazo(-z-y1)-3,5-di-phenytetrazoliumromide (MTT) assay, viable cell counting, flow cytometry (FCM), and enzyme-linked immunosorbant assay (ELISA). Results: We showed that the regenerated silk fibroin film was not cytotoxic to L929 cells and had no adverse influence on their adhesion, cell cycle or apoptosis; it had no adverse influence on the growth and VEGF secretion of ECV304 cells and no effect on the secretion of VEGF, Ang-1, PDGF and FGF2 by WI-38 cells. Conclusion: The regenerated silk fibroin film should be an excellent biomaterial with good cytocompatibility, providing a framework for reparation after trauma in clinical applications.